(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
The laundry industry is a significant and expanding sector that offers crucial services to individuals and families in Barangay Kaligayahan, Novaliches, Quezon City. Laundry services are an essential component of community life and are vital to preserving cleanliness and hygiene. To shed light on the factors that affect laundry enterprises’ operations, this study will explore the best practices and challenges faced by those operating in this particular area. Utilizing a descriptive quantitative research design, the study engages seventeen laundry owners through convenience sampling. This selection depends on the convenience of the participants who can provide initial data. Results highlight key findings. The majority of laundry owners surveyed reported that employees or staff are well-trained and enforce good personal hygiene practices among staff, including regular handwashing. With a mean score of 3.82, the respondents demonstrated strong agreement and positive engagement in this study. The laundry shop purchases reliable equipment from trustworthy suppliers and offers products and services that cater to different customer preferences. However, competing with other laundry services that offer lower prices affects the shop’s profitability. Lastly, this study found that maintaining an organized inventory of laundry supplies, detergents, and cleaning products is essential to ensure adequate stock levels and prevent shortages. It also highlights the importance of implementing effective pre-treatment procedures for heavily soiled items, stains, and delicate fabrics to achieve optimal cleaning results. In conclusion, this study revealed that laundry shops have efficient service, and laundry owners maintain cleanliness in the supply room, ensuring that the store is kept in a clean and dry area. The laundry shop’s preparation involves finding a location with a strong water supply and good access to their target market. Lastly, they prioritize customer satisfaction by providing excellent customer service and addressing inquiries promptly.